2019
DOI: 10.1186/s12912-019-0329-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of collective affective commitment in the relationship between work–family conflict and emotional exhaustion among nurses: a multilevel modeling approach

Abstract: Background Work–family conflict (WFC) is a crucial problem in nursing because of the demanding conditions of the job, such as strenuous shifts, physical and emotional workload, and intense patient involvement. Using a multilevel approach, this study investigated the moderating role of collective affective commitment as a protective resource in the relationship between WFC and emotional exhaustion. Methods The sample included 647 nurses from 66 working units in 4 Italian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 51 publications
3
55
1
Order By: Relevance
“…Individuals who experience work-family conflict can avoid the appearance of burnout when they have high organizational commitment. This is in line with previous studies which stated that organizational commitment moderates the influence of work-family conflict to burnout (Galletta, et al, 2019) Significant β2 and β3 values indicate that the organizational commitment variable is a quasi-moderator. Quasi moderator is a variable that moderates the relationship between the independent variables on the dependent variable which at the same time becomes an independent variable (Utama, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Individuals who experience work-family conflict can avoid the appearance of burnout when they have high organizational commitment. This is in line with previous studies which stated that organizational commitment moderates the influence of work-family conflict to burnout (Galletta, et al, 2019) Significant β2 and β3 values indicate that the organizational commitment variable is a quasi-moderator. Quasi moderator is a variable that moderates the relationship between the independent variables on the dependent variable which at the same time becomes an independent variable (Utama, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Hence, a multilevel model was used in the present study to assess hierarchically structured data. Multilevel modeling provides better statistical models that match real-world data, because it can address parameters that vary at more than one level, examine cross-level effects, and simultaneously decompose the variances of the variables into within-group and between-group components [13,22]. The two-level logistic model used in this study separated the effects of individual myopia from those of the average myopia in a class.…”
Section: Discussionmentioning
confidence: 99%
“…Myopia, which threatens visual quality and eye health, is a common refractive error among children and teenagers worldwide. Notably, the myopia prevalence is particularly high in east Asian countries; the prevalence in children 6-12 years of age is 53.9% in Tianjin, China [1], 36.7% in children aged 5-14 years in Beijing [2], 69.5% in teenage children in Singapore [3], 24.8% in 12-yearsolds in Malaysia [4], 22.6% in Korean children [5]. Studies have suggested that both genetic and environmental factors have a marked impact on myopia in school children.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this approach, professionals with a strong SOC are better capable to mobilize resources, appraise stressful situations as challenging and use effective problemsolving approaches in order to manage stress and to experience lower levels of the burnout (Kalimo et al 2003). This protective role of SOC on burnout was also demonstrated in previous studies among professionals such as teachers (Bracha and Bocos 2015), language therapists (Galletta et al 2019a(Galletta et al , 2019b and welfare workers (Steinlin et al 2017).…”
Section: Discussionmentioning
confidence: 66%
“…Within the context of job-related stressors, SOC is considered to be a crucial resource that may enhance professionals' adaptive reactions to the outcomes of challenging experiences (Kalimo et al 2003). Previous studies established a link between SOC and job burnout, particularly among therapeutic occupations (e.g., Bracha and Bocos 2015;Galletta et al 2019b;Levert et al 2000;Steinlin et al 2017). It seems that social support and high levels of SOC may protect professionals from the risks of burnout and their negative outcomes such as physical and emotional problems (Del-Pino-Casado et al 2018).…”
Section: Sense Of Coherence (Soc) and Burnoutmentioning
confidence: 99%